Examining Consumer Preferences and Willingness to Pay for Organic Vegetable Attributes: Using a Discrete Choice Experiment - Heptari Elita Dewi; Anisa Aprilia; Andrean Eka Hardana; Imaniar Ilmi Pariasa (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
This research aims to identify consumer attitudes toward organic green vegetables by estimating the degree of Willingness To Pay (WTP) for various attributes to evaluate the position of these organic vegetables and determine preferences for organic green vegetables based on income. This study used an online survey with 191 respondents on Java Island. The Discrete Choice Experiment was used to investigate product selection, WTP, and the relationship between the four characteristics of vegetables and income. The findings showed that consumers prefer organic and pesticide-free vegetables that are good for health, have low chemical emissions and a lower environmental impact, and are less expensive than non-organic vegetables. This is a challenge for producers and marketers to develop responsible input management strategies to produce high-quality vegetables at a low cost and with minimal environmental impact.